Serum zinc levels in acute psychiatric patients: A case series. (March 2018) - Joe, Peter; Getz, Mara; Redman, Samantha; Petrilli, Matthew; Kranz, Thorsten Manfred; Ahmad, Samoon; Malaspina, Dolores
Abstract: Zinc dysregulation is linked to neuropsychiatric disorders and a beneficial response to zinc supplementation has been demonstrated for depression. In this case series, we examined serum zinc levels with respect to clinical factors among 20 acutely ill psychiatric cases admitted to a large urban public hospital. The results showed frank clinical zinc insufficiency in a quarter of the subjects. Group-wise analyses showed a significant association between reduced serum zinc and diagnosis of depression, and reduced serum zinc in those with aggressive, assaultive, or violent behaviors. By contrast, relatively elevated zinc levels were observed in a subset of psychotic cases on antipsychotics and mood stabilizers who had no mood symptoms. In summary, clinical zinc insufficiency was common in these acutely admitted psychiatric cases. Zinc supplementation may ameliorate symptoms in certain cases and should be considered in treatment planning. A separate patient group had elevated zinc levels, which could conceivably be pathogenic. Larger studies are needed to confirm and extend this pilot data. Highlights: Serum zinc was measured in 20 acutely ill psychiatric inpatients. Reduced serum zinc may be a clinical significant marker of aggressive behavior. Low serum zinc was associated with major depression and treatment refractory psychosis. Serum zinc may be elevated in a subset of psychotic patients.